Predictors of impaired quality of life in patients with rheumatic diseases. Issue 7 (July 2016) - Anyfanti, Panagiota; Triantafyllou, Areti; Panagopoulos, Panagiotis; Triantafyllou, Georgios; Pyrpasopoulou, Athina; Chatzimichailidou, Sophia; Koletsos, Nikolaos; Botis, Ioannis; Aslanidis, Spyros; Douma, Stella
Abstract Quality of life (QoL) is a complex outcome and rheumatologic patients typically exhibit several comorbidities with a negative impact. In this study, we analyzed with respect to QoL for the first time a wide range of physical and psychological factors, including individual, clinical and disease-related parameters, mental health disorders, sexual dysfunction, and cardiovascular comorbidities among consecutive rheumatologic patients. QoL was evaluated using the EuroQol 5D (EQ-5D) utility index. The Health Assessment Questionnaire (HAQ) Disability Index, and the HAQ Pain Visual Analogue Scale were used as measures of physical disability and arthritis-related pain, respectively. The Hamilton Anxiety Scale and Zung Self-Rating Depression Scale, the International Index of Erectile Function and the Female Sexual Functioning Index were completed by all patients. In total, 360 patients were included, 301 females and 59 males. In the univariate analysis, pain, physical disability (p < 0.001 for both), disease duration (p = 0.014), anxiety and depression (p < 0.001 for both), as well as sexual dysfunction (p = 0.001 for females, p = 0.042 for males), correlated with QoL. Female sex (p < 0.001), advanced age (p = 0.029), lower educational level (p = 0.005), and cardiovascular factors (hypertension, dyslipidemia, diabetes, lack of systemic exercise) also appeared to negatively affect QoL. However, in the multiple regression model, only anxiety, pain, physical disability (p < 0.001 for all), and disease duration (p = 0.019) remained significant predictors of QoL. The emotional side and the disease-related physiological mode of rheumatic diseases appear as major independent correlates of QoL among rheumatologic patients, who may thus benefit the most from combined supportive psychological and pain-relieving interventions.